The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0160762
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Giardia lamblia: First Report of Assemblage B in Human Isolates from Rio de Janeiro (Brazil)

Abstract: BackgroundDespite the high prevalence of giardiasis, the genetic characterization of Giardia lamblia has been poorly documented in Brazil and molecular epidemiology research has only been conducted in the last few years. The aim of this study was to determine the prevalence of different G. lamblia assemblages and detect mixed infections among patients with giardiasis.Methods and Principal FindingsThe cross-section survey was conducted among patients attending the FIOCRUZ in Rio de Janeiro. In order to discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 42 publications
6
28
1
2
Order By: Relevance
“…The tpi gene PCR found 38 samples (55.07%) positive as assemblage B of G. intestinalis followed by assemblage A (28.98%), while the mix infection type (A + B) was detected in 11 samples making (15.94%). Similar trend of results was observed previously showing 64% assemblage B and 36% assemblage A in 2005 (20), 16% assemblage B and 10% assemblage A in 2013 (31), 67.9% assemblage B and 32.1% as assemblage A in 2016 (19) and 50.8% as type B followed by 27% as type A and 22.2% as mix types in 2017 (17). In contrast, a higher prevalence of assemblage A (54.8%) and (80%) was detected in 2011 and 2014, respectively (26,28).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The tpi gene PCR found 38 samples (55.07%) positive as assemblage B of G. intestinalis followed by assemblage A (28.98%), while the mix infection type (A + B) was detected in 11 samples making (15.94%). Similar trend of results was observed previously showing 64% assemblage B and 36% assemblage A in 2005 (20), 16% assemblage B and 10% assemblage A in 2013 (31), 67.9% assemblage B and 32.1% as assemblage A in 2016 (19) and 50.8% as type B followed by 27% as type A and 22.2% as mix types in 2017 (17). In contrast, a higher prevalence of assemblage A (54.8%) and (80%) was detected in 2011 and 2014, respectively (26,28).…”
Section: Discussionsupporting
confidence: 91%
“…Amplification of (SSU-rRNA) and (tpi) Genes for Detection of G. intestinalis: The extracted DNA was subjected to SSU-rRNA polymerase chain reaction using specific primers RH11 (5'-CATCCGGTCGATCCTGCC-3') and RH4 (5'-GTCGAACCCTGATTCTCCGCCAGG-3') to amplify a 292 bp product as described previously with slight modifications (19). The thermal cycler profiling was adjusted to 95°C for 05 min/1 cycle, 95°C for 30 sec/35 cycles, 58°C for 30 sec/35 cycles, 72°C for 45 sec/35 cycles and final extension at 72°C for 07 min/01 cycle using (Optimus 96G, Gradient Thermal Cycler, UK).…”
Section: Detection Of Giardia Intestinalis By Molecular Methodsmentioning
confidence: 99%
“…The results here show that the circulation of these assemblages is still current, with assemblage A being amplified throughout the environment by pets (Volotão et al, 2007;Fantinatti et al, 2018). However, the identification of assemblage B circulating in infected children had not been verified, although the first identification of assemblage B in Rio de Janeiro was reported in the same period (Faria et al, 2016). Further studies of environmental samples could help to understand the predominance of assemblage A.…”
Section: Discussionmentioning
confidence: 72%
“…The frequency of assemblage A was higher in comparison to B or E. The few reports addressing the Giardia assemblages in Brazil point to regional differences in the prevalence of the predominant circulating assemblage (Coelho et al, 2017). In Rio de Janeiro, the assemblage A has been most frequently identified in humans (Volotão et al, 2007;Fantinatti et al, 2016), although assemblage B (Faria et al, 2016) and assemblage E (Fantinatti et al, 2016) have already been reported. The present results are consistent and reinforce the reported epidemiological profile of the Giardia assemblages in our region.…”
Section: Discussionmentioning
confidence: 93%
“…However, in a study conducted in the UK the distribution of the assemblages A and B were different in relation to age group; equal distribution in children, assemblage B more common in young adults and assemblage A more common in adults over 50 [40]. Previous studies conducted in Rio de Janeiro, Brazil, found only assemblage A isolates, with the first assemblage B reported in 2016 [48]. All the samples from the present study originated from adults, and were predominantly identified as assemblage A.…”
Section: Discussionmentioning
confidence: 89%